Characterization of a temperature-sensitive Escherichia coli mutant and revertants with altered seryl-tRNA synthetase activity. - Ferri, M L (1997)
A mutation in the structural gene coding for seryl-tRNA synthetase in temperature-sensitive Escherichia coli K28 has been reported to alter the level of enzyme expression at high temperature (R. J. Hill and W. Konigsberg, J. Bacteriol. 141:1163-1169, 1980). We identified this mutation as a C-->T transition in the first base of codon 386, resulting in a replacement of histidine by tyrosine. The steady-state levels of serS mRNA in K28 and in the wild-type strains are very similar. Pulse-chase labeling experiments show a difference in protein stability, but not one important enough to account for the temperature sensitivity of K28. The main reason for the temperature sensitivity of K28 appears to be the low level of specific activity of the mutant synthetase at nonpermissive temperature, not a decreased expression level. Spontaneous temperature-resistant revertants were selected which were found to have about a fivefold-higher level of SerRS than the K28 strain. We identified the mutation responsible for the reversion as being upstream from the -10 sequence in the promoter region. The steady-state levels of serS mRNA in the revertants are significantly higher than that in the parental strain.